Optimization of force-limiting seismic devices connecting structural subsystems. (1st January 2016) - Scodeggio, Alessandro; Quaranta, Giuseppe; Marano, Giuseppe C.; Monti, Giorgio; Fleischman, Robert B.
Highlights: A seismic protection strategy that uncouples structural subsystems is considered. The force-limiting floor anchorage system is modeled using elasto-plastic springs. The optimal properties and positions of the connectors are determined numerically. Results for a 12-storey prototype reinforced concrete building are discussed. Abstract: This paper is focused on the optimum design of an original force-limiting floor anchorage system for the seismic protection of reinforced concrete (RC) dual wall-frame buildings. This protection strategy is based on the interposition of elasto-plastic links between two structural subsystems, namely the lateral force resisting system (LFRS) and the gravity load resisting system (GLRS). The most efficient configuration accounting for the optimal position and mechanical characteristics of the nonlinear devices is obtained numerically by means of a modified constrained differential evolution algorithm. A 12-storey prototype RC dual wall-frame building is considered to demonstrate the effectiveness of the seismic protection strategy.